2016
DOI: 10.1101/060137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High virulence does not necessarily impede viral adaptation to a new host: A case study using a plant RNA virus

Abstract: Background: Theory suggests that high virulence could hinder between-host transmission of microparasites, and that virulence therefore will evolve to lower levels. Alternatively, highly virulent microparasites could also curtail host development, thereby limiting both the host resources available to them and their own within-host effective population size. In this case, high virulence might restrain the mutation supply rate and increase the strength with which genetic drift acts on microparasite populations. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For example, in the case of the second virus released as a biocontrol against European rabbits in Australia -rabbit haemorrhagic disease virus (RHDV) -there is evidence that virulence has increased through time, probably because virus transmission often occurs through blow flies that feed on animal carcasses, making host death selectively favourable 46 . Similarly, experimental studies of plant RNA viruses have shown that high virulence does not necessarily impede host adaptation 47 and, in the case of malaria, higher virulence www.nature.com/nrg…”
Section: Theories Of Virulence Evolutionmentioning
confidence: 99%
“…For example, in the case of the second virus released as a biocontrol against European rabbits in Australia -rabbit haemorrhagic disease virus (RHDV) -there is evidence that virulence has increased through time, probably because virus transmission often occurs through blow flies that feed on animal carcasses, making host death selectively favourable 46 . Similarly, experimental studies of plant RNA viruses have shown that high virulence does not necessarily impede host adaptation 47 and, in the case of malaria, higher virulence www.nature.com/nrg…”
Section: Theories Of Virulence Evolutionmentioning
confidence: 99%